2022
DOI: 10.59141/jrssem.v1i11.202
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Product Quality and Brand Image Towards Buying Decisions with Buying Interest as Mediation Variable

Abstract: This research was conducted to find out empirical evidence of the role of buying interest in mediating product quality and brand image on purchasing decisions in the millennial generation in the Central Jakarta area, there is the online shop Matahari.com. The analysis method in this study uses structural equation modeling (SEM), sample of 225 respondents, the sampling technique refers to the calculation of Hair which is used for research with SEM analysis. The results showed that 1) Product quality had a posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…Based on the R-squared values criteria, which are 0.761 and 0.644, it can be concluded that the relationships between these variables fall into the strong category. This means that quality, price, e-wom, celebrity endorsement, brand image, and purchase intention have a relatively strong influence compared to other variables in this research model (Febrianti & Hasan, 2022). Based on the path analysis results, the effect of quality on purchase intention is significant at 0.180, with p-values less than 0.05, specifically at 0.027.…”
Section: Resultsmentioning
confidence: 79%
“…Based on the R-squared values criteria, which are 0.761 and 0.644, it can be concluded that the relationships between these variables fall into the strong category. This means that quality, price, e-wom, celebrity endorsement, brand image, and purchase intention have a relatively strong influence compared to other variables in this research model (Febrianti & Hasan, 2022). Based on the path analysis results, the effect of quality on purchase intention is significant at 0.180, with p-values less than 0.05, specifically at 0.027.…”
Section: Resultsmentioning
confidence: 79%